1987
DOI: 10.1295/polymj.19.157
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Prepared Polypyrroles from Aqueous Solutions

Abstract: ABSTRACT:Polypyrrole (PPy) films generated electrochemically from aqueous solutions have been found to have also good electrical conductivity. PPy films with the counter anions TsO-, so;, and NO; showed compact structure with apparent densities close to their flotation densities. The oxidative stability of PPy films has been compared by the value of the oxidation peak Epa around l.OV (vs. SCE) in the cyclovoltammogram. Prolonged electrolysis at +0.8V led to oxidative degradation. The temperature dependence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(41 citation statements)
references
References 18 publications
4
36
1
Order By: Relevance
“…Li has shown that the Py polymerization rate is directly proportional to the anion concentration of the monomer solution (for [A -] < 1 M). 23 For electrochemical PPy synthesis, various parameters such as the applied potential or the anodic current, 24 the concentration of monomer, 25 the nature of the supporting electrolyte, 26 and the nature of the working electrode 27 have an influence on the growth kinetics and the final structure of the polymer. 28,29 Polypyrrole nanostructures have been obtained using pyrrole solution containing either monohydrogenophosphate 28 or mixing of monohydrogenophosphate and dihydrogenophosphate (phosphate buffer solution (PBS)) [30][31][32][33][34][35] or carbonate.…”
Section: Introductionmentioning
confidence: 99%
“…Li has shown that the Py polymerization rate is directly proportional to the anion concentration of the monomer solution (for [A -] < 1 M). 23 For electrochemical PPy synthesis, various parameters such as the applied potential or the anodic current, 24 the concentration of monomer, 25 the nature of the supporting electrolyte, 26 and the nature of the working electrode 27 have an influence on the growth kinetics and the final structure of the polymer. 28,29 Polypyrrole nanostructures have been obtained using pyrrole solution containing either monohydrogenophosphate 28 or mixing of monohydrogenophosphate and dihydrogenophosphate (phosphate buffer solution (PBS)) [30][31][32][33][34][35] or carbonate.…”
Section: Introductionmentioning
confidence: 99%
“…72 The reversible redox chemistry of these polymers indicates that these materials may be used as thin flexible and robust electrodes in rechargeable storage batteries. [73][74][75][76] An advantage of using electroactive polymers rather than metals is that the charging and discharging reactions (redox doping and undoping) create charged carriers along the conjugated backbones and there is no deposition or dissolution of the electrode material.…”
Section: Energy Conversion: Battery Technologymentioning
confidence: 99%
“…In addition to these effects, which act at molecular level, bulk conductivity values are also dominated by electron transfer between grain boundaries and variations in morphology [30,31]. Thus, the bulk conductivity of a conjugated polymer may be described by Eq.…”
Section: Mechanism Of Electrical Conductionmentioning
confidence: 99%